High host specificity of alphacoronaviruses in Nearctic, insectivorous bats - Jonathon D. Kotwa; Arkadeb Bhuinya; Winfield Yim; Giulia Gallo; Pahul Singh; Qiang Liu; Anil Kumar; Emily Chien; Aaron Hou; Hsien-Yao Chee; Juliette Blais-Savoie; Lily Yip; et al. (npj Viruses)
Abstract Bats are reservoir hosts for a number of coronaviruses, some of which may pose spillover risks for humans and other animals. We detected two alphacoronaviruses in big brown bats (Eptesicus fuscus) and little brown myotis (Myotis lucifugus) in Ontario, Canada. These viruses are closely related to other coronaviruses circulating in bats in North America and also distantly related to human and swine coronaviruses. We found high similarity in the receptor-binding domain (RBD) in viruses derived from the same species of bat, but markedly lower in those derived from other species. We also functionally characterized the accessory protein ORF3 finding that ORF3 inhibited both IFNβ production and signaling. Our study provides insights into coronavirus diversity in bats in a previously under-sampled region. This work provides a baseline for in-depth surveillance to characterize the transmission dynamics of endemic coronaviruses in free-ranging wildlife, and for exploring the evolutionary relationships between coronaviruses and their hosts.